Association of Vitamin D receptor gene polymorphisms and serum 25-Hydroxy Vitamin D levels in vitiligo - A case-control study - Iffat Hassan; Yasmeen J bhat; Sabhiya Majid; Peerzada Sajad; Farhan Rasool; Rawoof A Malik; Inam Ul Haq (Wolters Kluwer Medknow Publications, 2019)
Background: Vitamin D has stimulatory and protective effects on melanocytes and acts through its nuclear vitamin D receptor (VDR) on target cells. Various single-nucleotide polymorphisms (SNPs) in VDR genes have been described. Aims: The aim was to study and compare the association of SNP of BsmI/Apa-I/TaqI/FokI/Cdx2 in VDR gene as well as the plasma vitamin D levels in vitiligo patients and healthy controls. Methods: This was a case-control study, in which 100 patients of vitiligo and an equal number of healthy individuals were studied. The VDR polymorphisms of Bsm I, Apa-I, TaqI, fok I, and cdx2 were investigated, after extraction of genomic DNA by rapid capillary polymerase chain reaction with melting curve analysis, and 25 hydroxy vitamin D levels were measured in cases and controls. Results: The frequency of genotypes (SNP FokI and cdx2) was higher in the patient group versus controls (P = 0.002). The genotype frequency (TaqI and Apa-I) was higher in the patients than the controls for the Tt genotype, but not significantly higher (48% vs. 39%, P= 0.1431). The difference between the groups in frequency of the genotype Aa(TaqI and Apa-I) was statistically significant (P = 0.0001 and P= 0.033). Statistically significant difference was also observed in Apa-I-evaluated alleles in cases when compared to controls (P = 0.0001). There was no significant difference in serum vitamin D levels between various genotypes among cases and controls. Out of 100 cases, 10 were found to have vitamin D levels of >30 ng/ml, 15 had levels between 20 and 30 ng/ml, 52 had ≤20 ng/ml, and 23 ≤ 10 ng/ml, respectively. Limitations: Since the skin biopsies were not taken from the lesions of vitiligo, the correlation of serum levels with tissue levels of VDR gene was not possible and the role of vitamin D supplementation was not evaluated. Conclusion: The single nucleotide gene polymorphisms of various VDR genes as found in the cases might lead to vitamin D deficiency, due to VDR dysfunction, which in turn could increase the susceptibility to develop vitiligo.